Manejo de la tecnología de la información y comunicación de los padres de familia de la Escuela de Educación Básica Paulo Freire, del Recinto Santa Isabel, Cantón Baba, Provincia de Los Ríos - Cercado Mariscal, Isabel Maria (2020)
This case study seeks to know "How is the management of information and communication technology of the Parents of the School of Basic Education" Paulo Freire ", of the Santa Isabel Campus, Baba Canton, Los Ríos Province, their The objectives are: to determine the management of Information and Communication Technologies that the Parents of the aforementioned campus have, also to identify the Information and Communication Technologies that parents handle and finally evaluate the Information and Communication Technologies used by them for effective support in the educational process of students. The applied methodology is field, descriptive, and bibliographic; For the collection of information, Surveys were applied to the 85 Parents of the Campus. The data obtained from the study shows that not all parents handle ICTs adequately. However, the Educational Campus has sought to help them, but this has not been enough because there are still parents who do not use these means for virtual classes; For this reason, it is recommended to continue training Parents with workshops and manuals, so that they learn, improve and expand their knowledge.